Incidence of community-acquired pneumonia among children under 5 years in Suzhou, China: a hospital-based cohort study - Tao Zhang; Jun Zhang; Jun Zhu; Genming Zhao; Lin Luan; Benfeng Zheng; Chen Qian; Qinghui Chen; Wanjing Lin; Zhaojing Li; Jianmei Tian (BMJ Open)
Objectives To depict the seasonality and age variations of community-acquired pneumonia (CAP) incidence in the context of the COVID-19 impact.Design Retrospective cohort study.Participants The observational cohort study was conducted at Soochow University Affiliated Children’s Hospital from January 2017 to June 2021 and involved 132 797 children born in 2017 or 2018. They were followed and identified CAP episodes by screening on the Health Information Systems of outpatients and inpatients in the same hospital.Outcome The CAP episodes were defined when the diagnoses coded as J09–J18 or J20–J22. The incidence of CAP was estimated stratified by age, sex, birth year, health status group, season and month, and the rate ratio was calculated and adjusted by a quasi-Poisson regression model. Stratified analysis of incidence of CAP by birth month was conducted to understand the age and seasonal variation.Results The overall incidence of CAP among children aged ≤5 years was 130.08 per 1000 person years. Children aged ≤24 months have a higher CAP incidence than those aged >24 months (176.84 vs 72.04 per 1000 person years, p<0.001). The CAP incidence increased from October, peaked at December and January and the highest CAP incidence was observed in winter (206.7 per 1000 person years, 95% CI 204.12 to 209.28). A substantial decline of CAP incidence was observed during the COVID-19 lockdown from February to August 2020, and began to rise again when the communities reopened.Conclusions The burden of CAP among children is considerable. The incidence of CAP among children ≤5 years varied by age and season and decreased during COVID-19 lockdown.